Nuclear and Radiological Emergencies: Biological Effects, Countermeasures and Biodosimetry - Elena Obrador; Rosario Salvador-Palmer; Juan I. Villaescusa; Eduardo Gallego; Blanca Pellicer; José M. Estrela; Alegría Montoro (MDPI AG, 2022)
Atomic and radiological crises can be caused by accidents, military activities, terrorist assaults involving atomic installations, the explosion of nuclear devices, or the utilization of concealed radiation exposure devices. Direct damage is caused when radiation interacts directly with cellular components. Indirect effects are mainly caused by the generation of reactive oxygen species due to radiolysis of water molecules. Acute and persistent oxidative stress associates to radiation-induced biological damages. Biological impacts of atomic radiation exposure can be deterministic (in a period range a posteriori of the event and because of destructive tissue/organ harm) or stochastic (irregular, for example cell mutation related pathologies and heritable infections). Potential countermeasures according to a specific scenario require considering basic issues, e.g., the type of radiation, people directly affected and first responders, range of doses received and whether the exposure or contamination has affected the total body or is partial. This review focuses on available medical countermeasures (radioprotectors, radiomitigators, radionuclide scavengers), biodosimetry (biological and biophysical techniques that can be quantitatively correlated with the magnitude of the radiation dose received), and strategies to implement the response to an accidental radiation exposure. In the case of large-scale atomic or radiological events, the most ideal choice for triage, dose assessment and victim classification, is the utilization of global biodosimetry networks, in combination with the automation of strategies based on modular platforms.